Information of the Eight Republican Conference of the Mathematicians of Lithuanian SSR - Journal , Lithuanian Mathematical (Lithuanian Mathematical Journal, 1967)
Информация о восьмой республиканской конференции математиков Литовской ССР Informacija apie Aštuntąją respublikinę Lietuvos TSR matematikų konferenciją